IDENTIFYING POTENTIAL ZONES FOR ECOTOURISM DEVELOPMENT IN BATTICALOA DISTRICT OF SRI LANKA USING THE GIS-BASED AHP SPATIAL ANALYSIS - Vyddiyaratnam PATHMANANDAKUMAR; Hong Ching GOH; Sheeba Nettukandy CHENOLI (Geo Journal of Tourism and Geosites, 2023)
Ecotourism makes a significant contribution to long-term development. However, a spatial analysis-based multicriteria process has been widely used in ecotourism development planning. Batticaloa district is one of the tourism hotspots in the country which distinctive views play a significant role in fostering the potential for ecotourism. However, no specific study or planning has been carried out to identify appropriate zones for ecotourism development. This study attempts to identify suitable zones for ecotourism development in Batticaloa District. In this research AHP method was used in GIS environment. Five thematic layers such as landscape, protected area, topography, accessibility, and community characteristics were given appropriate weights and integrated into the GIS through the weighted overlay analysis. Accordingly, five potential ecotourism zones were identified in the study area. The research revealed that the area very suitable for ecotourism development is largely distributed in the northern, western, and south-western parts of the Batticaloa district. Finally, 12.53% of the land area of the District falls under the “very suitable to extremely suitable" area for ecotourism development. The findings of this study can assist tourism planners and the government in precisely selecting locations for ecotourism development and relieving pressures on the region's tourism demand.